OPINIONS OF PRIMARY SCHOOL TEACHERS ON THE DEFINITION, IDENTIFICATION AND EDUCATION OF GIFTED CHILDREN - Ahmet BİLDİREN (International Journal of Eurasia Social Sciences, 2018)
Identification and education of gifted children have gained increased importance in our day. Gifted children who are part of the education system in Turkey are nominated by their primary school teachers for identification at the Science and Arts Centers in order to receive special education. The objective of this study was to determine the opinions of primary school teachers regarding the definition, identification and education of gifted children. The sample group of the study was comprised of a total of 13 primary school teachers. Phenomenology pattern was used for an in-depth and detailed examination of the perceptions, tendencies and experiences of primary school teachers on the definition, identification and education of gifted children. The opinions of primary school teachers have been examined under the heading of the definition, identification and education of gifted children and common themese have been formed. It was determined as a result of the study that primary school teachers define gifted children according to their mental talent, special talent, creativity and social communication, that they ascribe the task of identifying gifted children to the families of children, themselves and mostly to specialists.